Strongly enhanced dielectric and energy storage properties in lead-free perovskite titanate thin films by alloying. (March 2018) - Cho, Seungho; Yun, Chao; Kim, Yoon Seo; Wang, Han; Jian, Jie; Zhang, Wenrui; Huang, Jijie; Wang, Xuejing; Wang, Haiyan; MacManus-Driscoll, Judith L.
Abstract: Lead-free perovskite oxide thin films prepared by alloying of titanates and materials with lower melting points are shown to have enhanced ferroelectric and dielectric properties. BaTiO3 (or SrTiO3 ) with 25% addition of BiFeO3 has much improved crystalline perfection because of the lower melting point of the BiFeO3 giving enhanced growth kinetics. The maximum dielectric peak temperature of BaTiO3 is increased by ~ 200 °C and leakage currents are reduced by up to a factor of ~ 100. The loss tangent reduces up to 300 °C, with a factor of > 14 reduction at room temperature. The dielectric breakdown strength is higher by a factor of ~ 3 (> 2200 kV cm −1 ) and from room temperature up to 500 °C the dielectric constant is > 1000. Also, a low variation of dielectric constant of ~ 9% from room temperature to 330 °C is obtained, compared to ~ 110% for BaTiO3 . The maximum polarization ( P max ) is double that of BaTiO3, at 125.3 μC cm −2 . The film has high energy storage densities of > 52 J cm −3 at 2050 kV cm −1, matching Pb-based ferroelectric films. The strongly improved performance is important for applications in energy storage and in high temperature (up to 300 °C) capacitors as well as wider application in other electronic and energy technologies. Graphical abstract: fx1 Highlights: High crystallinity is achieved by mixing titanate with a lower melting point material. The film with enhanced crystallinity has strongly enhanced dielectric properties. The film has high energy storage densities of > 52 J cm −3, matching Pb-based films.